LEGITIMASI ZAKAT PROFESI DALAM PERSPEKTIF EKONOMI ISLAM - Ali, Isnu Cut (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
Professional zakat is a form of zakat that is collected on income generated from a particular job or profession. They argue that there is no clear basis in the Quran or Sunnah that expressly imposes zakat on professional income, so determining professional zakat is considered an effort that may not be in accordance with sharia, which refers to several reasons, including indicating its generality. verses relating to the obligation of zakat and the principle of justice in the distribution of assets. The need to help those who are less fortunate. Meanwhile, there are also ulama who reject the obligation to pay professional zakat, on the grounds that zakat money is only imposed on certain assets such as gold, silver and agricultural products. They argue that there is no clear basis in the Qur'an or Sunnah that expressly imposes zakat on professional income, so determining professional zakat is considered ijtihad which is not necessarily in accordance with sharia.